A Review on the Management of Biliary Complications after Orthotopic Liver Transplantation - Moy, Brian T. (J Clin Transl Hepatol, 2018)
Orthotopic liver transplantation is the definitive treatment for end-stage liver disease and hepatocellular carcinomas. Biliary complications are the most common complications seen after transplantation, with an incidence of 10–25%. These complications are seen both in deceased donor liver transplant and living donor liver transplant. Endoscopic treatment of biliary complications with endoscopic retrograde cholangiopancreatography (commonly known as ERCP) has become a mainstay in the management post-transplantation. The success rate has reached 80% in an experienced endoscopist’s hands. If unsuccessful with ERCP, percutaneous transhepatic cholangiography can be an alternative therapy. Early recognition and treatment has been shown to improve morbidity and mortality in post-liver transplant patients. The focus of this review will be a learned discussion on the types, diagnosis, and treatment of biliary complications post-orthotopic liver transplantation.